STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYATLEGENDA MAKAM KERAMAT SYEKH IBRAHIM MUFTI DINAGARI TARAM KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA - Zahara, Pipin; Nurizzati, Nurizzati; Nst., Bakhtaruddin (Jurnal Bahasa dan Sastra, 2018)
The purposes of this study were to describe the structure and social function of folklore legend Makam Keramat Syekh Ibrahim Mufti in Nagari Taram, Harau, District of Lima Puluh Kota. The data of this study were structure and social function of folklore legend Makam Keramat Syekh Ibrahim Mufti in Nagari Taram, Harau, District of Lima Puluh Kota. The data were analyzed by using the following procedures: (1) the stage of data description is translate the data into Indonesian, (2) the stage of data classification/analysis, (3) the stage of the discussion and conclusions of the results of the classification or data analysis, and (4) reporting stage. It can be concluded that the structure and social function of folklore legend Makam Keramat Syekh Ibrahim Mufti in Nagari Taram, Harau, District of Lima Puluh Kota consist of the character, plot, and setting. In addition, the function social ofÂ  in Nagari Taram, Harau, District of Lima Puluh Kota, are: (1) to educate, (2) bequeath, (3) identity, and (4) tradition.Keywords: structure, social function, folklore, legend